THE INFLUENCE OF EMOTIONAL INTELLIGENCE ON THE ACCOUNTING COMPREHENSION: GENDER BASED STUDY - Sinarti Sinarti; Ulfa Dwi Mustika Sari (Pusat P2M Politeknik Negeri Batam, 2017)
The purpose of this research is to examine the influence of emotional intelligence on the level of accounting comprehension and to examine the difference of emotional intelligence and accounting comprehension between male and female accounting students. Emotional intelligence is measured by five components which is self-awareness, self-regulation, motivation, empathy, and social skills. Accounting comprehension is measured by accounting subject grade, consist of accounting principles, intermediate accounting, advanced financial accounting, auditing and accounting theory. Sampling method in this research using purposive sampling. Linier analysis and t-test independent are used as a data analysis technique. The results show that emotional intelligence has an effect on accounting comprehension, and there is no difference of emotional intelligence and a difference of accounting comprehension between male and female students. This research only using emotional intelligence in measuring accounting comprehension and there is a different number of male and female respondents. The future research may added more variable such as learning behavior.